2013
DOI: 10.1016/j.juro.2013.02.3200
|View full text |Cite
|
Sign up to set email alerts
|

Penile Measurements in Tanzanian Males: Guiding Circumcision Device Design and Supply Forecasting

Abstract: Our descriptive study provides penile measurements of males who sought voluntary medical male circumcision services in Iringa, Tanzania. To our knowledge this is the first study in a sub-Saharan African population that provides sufficiently detailed glans and foreskin dimensions to inform voluntary medical male circumcision device development and size forecasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…None of the studies had used inter‐rater reliability when taking measurements. Some described training procedures to ensure consistency between different raters . Some described repeated measures used to ensure accuracy .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the studies had used inter‐rater reliability when taking measurements. Some described training procedures to ensure consistency between different raters . Some described repeated measures used to ensure accuracy .…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of all studies extracted for inclusion are shown in Table 1 [5][6][7][8][9][10]12,13,16,[18][19][20][21][22][23][24][25][26][27][28].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age was categorised into 8–13, 14–18 and >18 years based on data from Sub-Saharan Africa on Tanner staging in males undergoing circumcision. [ 23 ]…”
Section: Methodsmentioning
confidence: 99%
“…In a study of 3,300 young Italian men (none with abnormalities of the penis), the median length was 4.92 inches (12.5 cm) (Ponchietti et al, 2001). Ten other studies similarly reported mean stretched lengths of less than 5 inches (12.7 cm) (Chen et al, 2000;Choi et al, 2011;Chrouser et al, 2013;Mehraban, Salehi, & Zayeri, 2007;Promodu et al, 2007;Şengezer et al, 2002;Siminoski & Bain, 1993;Son, Lee, Huh, Kim, & Paick, 2003;Spyropoulos et al, 2002;Wessells et al, 1996), while 10 others reported mean lengths of 5.08 to 5.63 inches (12.9 to 14.3 cm) (Aslan et al, 2011;Awwad et al, 2005;Kamel, Gadalla, Ghanem, & Oraby, 2009;Khan, Somani, Lam, & Donat, 2012;Savoie, Kim, & Soloway, 2003;Schonfeld & Beebe, 1942;Shah & Christopher, 2002;Shalaby, Almohsen, El Shahid, Abd Al-Sameaa, & Mostofa, 2015;Sӧ ylemez et al, 2012;Yafi et al, 2018).…”
Section: Studies In Which Researchers Measured Stretched Penisesmentioning
confidence: 96%